👤

Se considera nr. reale x, y ≠ 0. Calculati :
[tex] {x}^{2} \times {x}^{2} + {x}^{3} \times x + 3 \times {x}^{3} = \\ {x}^{6} \div {x}^{3} - x \times x \times x + {x}^{7} \div {x}^{4} = \\ ( {x}^{2}) ^{4} \div {x}^{5} + {3x}^{3} \times 2 - x \times {x}^{2} = \\ ( {y}^{4} )^{3} \div ( {y}^{2} )^{5} + (3y) ^{2} - 2 \times {y}^{4} \div {y}^{2} = \\ {x}^{15} \div ( {x}^{2} )^{5} \div x + ( {2x}^{2} ) ^{2} - {x}^{2} \times {x}^{2} = \\ ( - y)^{2} + {2y}^{2} + {y}^{6} \div ( - y)^{4} .[/tex]


Răspuns :

1) = x^4 + x^4 + 3x^3 = 2x^4 + 3x^3 
2) = x^3 - x^3 + x^3 = x^3 
3) = x^8 : x^5 + 6x^3 - x^3 = x^3 + 6x^3 - x^3 = 6x^3 
4) = y^12 : y^10 + 9y^2 - 2y^2 = y^2 +7y^2 = 8y^2 
5) = x^15 : x^10 : x + 4x^4 - x^4 = x^4 + 4x^4 - x^4 = 4x^4 
6) = y^2 + 2y^2 + y^2 = 4y^2